Letter (copy) : Wencaslao Carrillo - Tewson, Vincent
026-0027-001 INTERNATIONAL. HVT/EAB. 2nd August 1939. Mr. Thomas McKenna, O.B.E., International Metalworkers' Federation, 93, Borough Road West, MIDDLESBROUGH. Dear Mr. McKenna, WENCASLAO CARRILLO. Many thanks for your letter of the 31st July regarding Wencaslao Carrillo, who is now resident in this country, and the possibility of bringing his two younger children from Oran to join him here. We have already made an application to our Home Office for visas to be granted to the two children to enable them to come to this country, but up to the moment we have not received any reply. We can quite appreciate the anxiety of Comrade Carrillo to have his children with him, and we will do everything possible to get the matter settled as quickly as possible. As soon as we have anything further to report we will write you again. Yours sincerely, Assistant Secretary. 292/946/26/27